Emission of neutrino-antineutrino pairs by hadronic bremsstrahlung processes - Bacca Sonia; Sharma Rishi; Schwenk Achim (EPJ Web of Conferences, 2016)
We review our recent calculations of neutrino-antineutrino pair production from bremsstrahlung processes in hadronic collisions at temperature and densities relevant for core-collapse supernovae. We focus on neutron-neutron and neutron-α collisions.